New Dimensions of Brønsted Base Catalyzed Carbon–Carbon Bond-Forming Reactions - Yamashita, Yasuhiro; Kobayashi, Shū (Synlett, 2021)
Catalytic carbon–carbon bond-forming reactions of weakly acidic carbon pronucleophiles (pKa in DMSO ≥30) were developed using strong alkaline metal Brønsted bases as catalysts. Not only weakly acidic amides, esters, nitriles, sulfonamides without any activating group, and alkyl azaarenes, but also alkyl arenes such as toluene, were applicable for the reactions, which are difficult to be applied in typical Brønsted base catalyzed reactions. Expansion to enantioselective reactions was also revealed to be possible. The reactions are atom economical and require only inexpensive alkaline metals rather than precious transition metals.1 Introduction2 Catalytic Direct-Type Addition Reactions of Weakly Acidic Carbonyl and Related Pronucleophiles3 Catalytic Direct-Type Addition Reactions of Alkyl Azaarenes4 Catalytic Direct-Type Addition Reactions of Alkyl Arenes5 Conclusion
Keywords: strong base; catalysis; asymmetric; alkaline metal; carbon–carbon bond formation